Customers' acceptance of food served in Malay restaurants during COVID-19 pandemic: study on food quality factors / Noorliza Zainol ... [et al.] - Zainol, Noorliza; Ariffin, Hashim Fadzil (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
COVID-19 outbreak has presented the highly infectious novel coronavirus and has created pertinent questions about the present and future survival of restaurant sector. This research addresses customer acceptance of food being served in Malay restaurants during the COVID-19 pandemic. The research design used in this study is quantitative research. A total of 357 respondents were involved in this study. This research used the G-power to collect data and the data was analysed using SPSS version 26. The respondents of this study are customers of Malay-concept restaurants in Pulau Pinang. The set of questionnaires consists of 2 sections which are section a) demographic profile; b) customer acceptance of food being served in Malay restaurants during the COVID-19 pandemic. A 5-point Likert-type scale that ranged from 1 (strongly disagree) to 5 (strongly agree) was used in this study to measure food quality such price fairness, presentation of food, and taste. The outcome of the study show that Malay restaurant owners need to carefully plan their business operations to ensure that the restaurants are able to sustain in difficult times such as in this COVID-19 pandemic. Limitations and scope of future research are also discussed.